Chlorogenic acid inhibits virulence and resistance gene transfer in outer membrane vesicles of carbapenem-resistant Klebsiella pneumoniae - Wang, Wen-Ba; Wan, Jia-Yang; Yu, Dao-Jun; Du, Hai-Xia; Zhou, Hui-Fen; Wan, Hai-Tong; Yang, Jie-Hong (Frontiers in Pharmacology, 2025)
IntroductionCarbapenem-resistant Klebsiella pneumoniae (CRKp) infection poses a significant global public health challenge, with the misuse of antibiotics further contributing to the development of resistance and triggering harmful inflammatory responses. Outer membrane vesicles (OMVs) released by CRKp under sub-lethal concentration of MEM pressure (KOMV-MEM) exhibit enhanced virulence and greater efficiency in transferring resistance genes.MethodsWe investigated the inhibitory effects of chlorogenic acid (CA) on KOMV-MEM characteristics and its protective role in KOMV-MEM infected mice. Based on LC-MS proteomic analysis of vesicles, we screened for potential targets of KOMV-MEM in promoting macrophage (MØ) pyroptosis pathways and inducing resistance gene transfer. Subsequently, computational predictions and experimental validation were performed to determine how CA regulates these mechanisms.ResultsThis study confirmed that, under MEM pressure, the exacerbated infection levels in CRKp-inoculated mice are attributable to the high virulence of KOMV-MEM. Computational and experimental results demonstrated that CA inhibits pyroptosis by reducing MØ capture of KOMV-MEM through blocking the interaction between GroEL and LOX-1. Furthermore, CA prevents the spread of resistance genes by disrupting the conjugation and transfer processes between KOMV-MEM and recipient bacteria. Finally, in vitro and in vivo assays showed that CA inhibits KOMV-MEM resistance enzymes, thereby preventing the hydrolysis of MEM in the environment and depriving susceptible bacteria of protection.DiscussionThese findings provide the first confirmation that CA can inhibit both the virulence and the transmission of drug resistance in KOMV-MEM. This underscores the potential of CA treatment as a promising antimicrobial strategy against CRKp infection.